(untitled) (Research, Society and Development, 2023)
This article aims to describe the teaching about Florence Nightingale mediated by technologies in the History of Nursing discipline. It is a proposal for an experience report, with a qualitative approach of the descriptive type, with a view to sharing experiences in the use of technologies in academic teaching of the undergraduate course in Nursing at Universidade Federal Fluminense for nursing students in the 1st period. This article is based on the following discussions: Teaching Mediated by Technologies (TMT) about Florence Nightingale; The Environment according to Florence in the TMT. Teaching Mediated by Technologies enables an understanding of the content taught by the teacher, making it attractive and current, facilitating understanding and student participation in the teaching-learning process. Therefore, the teacher as a mediator of knowledge has the opportunity to contextualize content in face-to-face teaching mediated by technologies that stimulate the student to research and the visibility of Nursing as a profession through Florence Nightingale in the current world.